REDESIGN GENERATOR LANDING CRAFT TANK 1500 DWT DENGAN MEMPERTIMBANGKAN FAKTOR TEKNIS DAN EKONOMIS - Ivan Guntur Perdana (2021)
The electrical system is a very important thing on a ship, where the tool that functions as a power generator to meet the electricity needs on the ship is a generator. In some cases, generator planning does not pay attention to technical and economic factors that have an impact on operating costs to be expensive. In writing the thesis, the author will examine the redesigning of the 1500 DWT Landing Craft Tank (LCT) generator by considering technical and economic factors. The technical factor will be adjusted to the standards and provisions of the Classification Board, while the economic factor will be planning an efficient electrical installation and power installation system to provide material needs. The results obtained from this paper show the operational needs of the ship based on the condition of the ship when harbour, sailing, loading and unloading, and emergency during the day with a total intermittent load of 110,6 KW and a total continuous load of 130,6 KW while the operational needs of the ship at night with the total intermittent load is 98,2 KW and the total continuous load is 181,5 KW. Then it was found that the largest operational power requirement of the ship in an emergency at night was 38,5 KW and the largest power was in the condition of the ship at night of 102,5 KW. Then we get 3 generators with 2 sets of 60 KW power capacity and 1 set of 45 KW.